A Human Rights Agenda for the Biden Administration. (22nd January 2021) - Cleveland, Sarah H.
Abstract : The Biden administration has much to do to restore the United States' credibility as a human rights leader and to strengthen the human rights system in an era of rising right-wing nationalism, authoritarianism, and competition for global power. In doing so, it needs to lead by example by putting its own house in order, and act with both courage and humility in the face of deep global skepticism and distrust. Specifically, the administration should pursue five stages of engagement on human rights: reverse and revoke measures taken by the Trump administration, reaffirm the United States' traditional commitments to human rights at home and abroad, rebuild the State Department and diplomatic corps, reengage with international and regional mechanisms through bilateral and multilateral diplomacy, and reconceptualize the United States' twenty-first century relationship to human rights. All of the other topics addressed in this symposium—climate, health, elections, migration, structural racism, and trade—implicate human rights. None can be adequately addressed without a robust U.S. human rights agenda.